2018
DOI: 10.17219/acem/65787
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to hepatitis E virus, hepatitis A virus and Borrelia spp. infections in forest rangers from a single forest district in western Poland

Abstract: We failed to unequivocally prove HEV exposure in FRs. The HAV seroprevalence in this study paralleled the situation in the general population. Exposure to Borrelia spp. in FRs was common.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Seroepidemiological studies conducted among forestry workers in Europe showed seropositivity of 31% in France (2002-2003)[ 11 ] and 18% in Germany (Brandenburg, 2008)[ 21 ]. In more recent studies, HEV antibodies were detected in 2.2% of forest rangers from western Poland (Poznan, 2014)[ 10 ], 5% of forestry workers from eastern Poland (Lubelskie Voivodship, 2014-2015)[ 13 ], and 14% of forestry workers in Italy (Trentino-Alto Adige Region, 2014-2015)[ 12 ]. Although forestry workers have been identified as being at risk of HEV infection in several studies, the French study revealed for the first time that woodcutters are at a particularly high risk of infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seroepidemiological studies conducted among forestry workers in Europe showed seropositivity of 31% in France (2002-2003)[ 11 ] and 18% in Germany (Brandenburg, 2008)[ 21 ]. In more recent studies, HEV antibodies were detected in 2.2% of forest rangers from western Poland (Poznan, 2014)[ 10 ], 5% of forestry workers from eastern Poland (Lubelskie Voivodship, 2014-2015)[ 13 ], and 14% of forestry workers in Italy (Trentino-Alto Adige Region, 2014-2015)[ 12 ]. Although forestry workers have been identified as being at risk of HEV infection in several studies, the French study revealed for the first time that woodcutters are at a particularly high risk of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Professionally exposed individuals ( e.g., forestry workers, veterinarians, hunters, farmers) are also at increased risk of getting infected by HEV. Detected HEV seroprevalence rates in professionally exposed workers differ greatly between countries: Forestry workers (2.2%-31.0%)[ 10 - 13 ], hunters (3.81%-22.2%)[ 13 - 15 ], and veterinarians (10.2%-43.7%)[ 16 , 17 ]. In the transplant population, HEV seroprevalence rates were reportedly between 6.0% and 29.6%[ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Twenty-three articles reported seroprevalence of LB in seven Eastern European countries ( Table 1 ) (Bazovska et al 2005 , Rojko et al 2005 , Hajek et al 2006 , Biletska et al 2008 , Cisak et al 2008 , Buczek et al 2009 , Bazovská et al 2010 , Podsiadly et al 2011 , Lakos et al 2012 , Machcińska et al 2013 , Kocbach and Kocbach 2014 , Tokarska-Rodak et al 2014 , Zákutná et al 2015a , 2015b , Kuchynka et al 2016 , Magnaval et al 2016 , Zając et al 2017 , Bura et al 2018 , Bušová et al 2018 , Kiewra et al 2018 , Kříž et al 2018 , Pańczuk et al 2019 , Pawelczyk et al 2019 ). National seroprevalence estimates using a single-tier testing strategy on healthy persons and/or indoor workers were 5% in Poland (ELISA IgG, healthy blood donors) (Pawelczyk et al 2019 ), 9.7% in Slovenia (ELISA IgG) (Rojko et al 2005 ), 10.3% in Russia (ELISA IgG) (Magnaval et al 2016 ), and 34.3% in Ukraine (IFA IgG+IgM) (Biletska et al 2008 ).…”
Section: Resultsmentioning
confidence: 99%
“…Five studies (Bazovska et al 2005 , Cisak et al 2008 , Tokarska-Rodak et al 2014 , Kuchynka et al 2016 , Pańczuk et al 2019 ) used the IgG and IgM standard two-tier test; the weighted mean of the high-risk group was higher (40.6%) than in the low-risk group (11.1%). Four of 23 studies (Podsiadly et al 2011 , Kocbach and Kocbach 2014 , Bura et al 2018 , Kiewra et al 2018 ) measured IgG in high-risk populations only, giving a weighted mean of 24.7%. When stratified by single-tier testing (IgM and IgG), seroprevalence was higher in high-risk groups (37.2%) than low-risk groups (34.7%).…”
Section: Resultsmentioning
confidence: 99%
“…The main pertinent route of human infection is the fecal – oral, through consumption of meat, liver, and offal originating from infected wild boars [ 34 , 35 ]. Direct contact with infected animals also seems to be important, as the presence of anti-HEV antibodies has been detected more often among hunters and forest workers [ 21 , 36 , 37 , 38 , 39 ]. The phylogenetic analysis of the ORF2 sequences of the detected Polish wild boar HEV strains showed their affiliation to the third virus genotype.…”
Section: Discussionmentioning
confidence: 99%